The second order confirmatory factor analysis in deciding to visit the beaches, Phetchaburi Province: from the concept of marketing mix - Rittiboonchai, Witit; U- Thairatana, Pichaya (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The purposes of this research were to 1. Compare the decision to visit the beach, Phetchaburi province. From marketing mix concepts classified by personal factors and 2. Analyze the second confirmatory element in deciding to visit the beach in Phetchaburi Province from the marketing mix concept. Data had been collected from Thai tourists and foreign tourists (spend overnight) in the province of 2,827,527 people, using the sample size-based Yamane’s formula. 400 of sampling people were selected by Quota tool. The tool for collecting data is questionnaires that passed content validity and finding the precision. The statistics used in data analysis consisted of percentage, mean, standard deviation, t-test, one-way analysis of variance and the second order confirmatory factor analysis. The results of the research are as follows: 1.The decision to visit the beach in Phetchaburi province from the concept of marketing mix, there are differences when classified by race, age, education level, occupation and income with statistical significance. 2. The results of the first confirmatory factor analysis in deciding to visit the beach in Phetchaburi province from the marketing mix concept was found that the Place, product and marketing promotion respectively, while the second confirmatory element analysis in deciding to visit the beach, Phetchaburi province, from the concept of marketing mix in term of Place, found that due to the convenience of traveling, the cleanliness of tourist attractions and the value of natural beauty.